Detecting Pulmonary Nodules in Lung Cancer Patients Using Whole Body FDG PET/CT, High-resolution Lung Reformat of FDG PET/CT, or Diagnostic Breath Hold Chest CT - Flavell, Robert R; Behr, Spencer C; Mabray, Marc C; Hernandez-Pampaloni, Miguel; Naeger, David M (Academic radiology, 2016)
Pulmonary nodules can be missed on the non-breath hold computed tomography (CT) portion of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT), and for this reason prior studies have advocated for routinely performing dedicated breath hold CT of the chest in addition to PET/CT for routine staging of malignancy. We evaluated the rate of pulmonary nodule detection on standard CT images from whole body PET/CT studies (WB-PET/CT), high-resolution lung reconstruction CT images from PET/CT studies (HR-PET/CT), and diagnostic breath hold chest CT (BH-CT). A cohort of 25 patients was identified who had a history of lung cancer as well as a PET/CT staging or restaging scan and BH-CT within 30 days of each other. All PET/CTs included a set of CT images using a soft tissue algorithm filter and 3.75- to 5-mm slice thickness, as well as high-resolution reformats with a sharp reconstruction filter and 2-mm slice thickness. The CT images from WB-PET/CT, HR-PET/CT, and BH-CT were reviewed by three radiologists. Significance was analyzed by two-way repeated measures analysis of variance. There were 2.84 nodules found per patient with WB-PET/CT, 3.85 nodules with HR-PET/CT, and 3.91 nodules with BH-CT. When only nodules less than or equal to 8 mm in size were considered, WB-PET/CT also demonstrated significantly fewer nodules (1.98) compared to the HR-PET/CT (2.94) or a BH-CT (2.86) (P < 0.001). No difference in detection rate was noted between the two higher resolution modalities. More pulmonary nodules are detected on the CT portion of PET/CT studies when high-resolution reformatted images are created and reviewed. The ability to detect nodules with the reformatted images was indistinguishable from dedicated BH-CT. Overall, high-resolution reformats of PET/CT images of the lungs can increase the sensitivity for pulmonary nodule detection, approaching that of dedicated BH-CT. These data suggest that if HR-PET/CT reformats are used, additional dedicated BH-CT is unnecessary for routine staging of lung cancer.